2021
DOI: 10.21009/pinter.5.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Strategi Pembelajaran Peer Tutoring Dalam Meningkatkan Self-Regulated Learning (Srl) Pada Mata Pelajaran Platform Komputasi Awan Kelas Xi Sistem Informasi Jaringan Dan Aplikasi SMK Negeri 26 Jakarta

Abstract: Penelitian ini bertujuan untuk mengetahui efektivitas peningkatan self-regulated learning siswa kelas XI Sistem Informasi Jaringan dan Aplikasi SMK Negeri 26 Jakarta setelah diberikan treatment strategi pembelajaran peer tutoring pada mata pelajaran platform komputasi awan. Penelitian ini dilakukan di SMK Negeri 26 Jakarta, dilaksanakan pada bulan April – Mei 2019. Metode penelitian yang digunakan adalah quasy eskperimental yang diberikan perlakuan berupa strategi pembelajaran peer tutoring pada kelas ekperime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These findings have been confirmed through the behavioral aspect of the study. According to Azizah et al (2021), the behavioral component of self-regulated learning involves an individual's capacity to regulate or control their learning needs, including preparing tasks, developing strategies, evaluating, and improving. Fasikhah and Fatimah (2013) also observed that seeking assistance is one of the behaviors exhibited during self-regulated learning, along with organizing one's schedule and study environment.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have been confirmed through the behavioral aspect of the study. According to Azizah et al (2021), the behavioral component of self-regulated learning involves an individual's capacity to regulate or control their learning needs, including preparing tasks, developing strategies, evaluating, and improving. Fasikhah and Fatimah (2013) also observed that seeking assistance is one of the behaviors exhibited during self-regulated learning, along with organizing one's schedule and study environment.…”
Section: Discussionmentioning
confidence: 99%